Cover Feature: A Study of 3, 5‐Dinitro‐1‐(2, 4, 6‐trinitrophenyl)‐1H‐pyrazol‐4‐amine (PicADNP) as a New High Energy Density Booster Explosive (13/2021). Issue 13 (26th March 2021) - Bauer, Daniel; Dosch, Dominik E.; Fuchs, Veronika; Karaghiosoff, Konstantin; Klapötke, Thomas M.
Abstract : The Cover Feature shows a historical photography of a large‐scale explosive test as well as the expanding blast wave, which was taken by D. R. Richmond (US Army). The photography is complemented by pictures of the synthetic pathway, the crystal structure and the calculated Hirshfeld surface of 3, 5‐dinitro‐1‐(2, 4, 6‐trinitrophenyl)‐1H‐pyrazol‐4‐amine (PicADNP), a new high energy density booster explosive. This exciting material exhibits an increased thermal stability and lower sensitivities towards external stimuli than the state‐of‐the‐art material PETN, while maintaining a comparable performance. More information can be found in the Full Paper by T. M. Klapötke et al.